Risk and uncertainty in land purchase on credit in Marcos Juarez settlements, Cordoba, in the late 19th century (Quinto Sol, 2018)
This article analyses the settlement of the Marcos Juarez district in the Province of Córdoba by the sale of land on credit in the late 19th century. First, the area of the Department and Province where such settlement took place is determined. Then, the basic characteristics of the primary market in the researched area are described. Also, the basic characteristics of sale-on-credit contracts are reviewed as well as the readjustments introduced due to the 1890 crisis. The focus is on the use of land as collateral and the consequences of this practice on the researched sales operations. In this respect, emphasis is placed on the costly consequences for farmers who could not meet payments, including the loss of partial redemption of loans as well as any improvements made on the land. Finally, the article breaks down the components of the settlers’ income by analysing harvest yields and wheat prices. It also tries to determine the relation between yields and farming skills.
Keywords: economic history; agricultural history; contracts; Córdoba